Factors promoting and impeding foreign language learning process (Eurasian Journal of Philology Science and Education, 2016)
Learning a foreign language is not a homogeneous process. It is impossible to predict or guarantee success, since the results of training differ in character. In this article we examine some logical factors which can promote or impede fruitful study of a foreign language. For a long time in literature acquisition of foreign languages was considered as the process similar to the development of children’s speech. But over time, as a result of many experiments, the authors concluded that the study of a foreign language by adults is fundamentally different from the system of children’s speech. Already in adolescence the internal mechanism of the development of children’s speech ceases to operate, and it is this factor which explains why the study of a foreign language often turns into a complicated and not always successful enterprise. Especially this problem occurs when a foreign language is taught exclusively in classroom conditions, in the absence of a language environment.
Keywords: variation in degree of success; interference; transference; affective factor; motivation.